(untitled) - Negus, Christopher (Indianapolis, IN, 2011)
Linux is an excellent, low-cost alternative to more expensive operating systems and its popularity continues to remain on the rise. This comprehensive resource offers more than 100 pages of the most sought-after Linux commands, provides new tutorial chapters aimed specifically at Windows desktop users and Windows administrators, and includes a new chapter on using Linux on gadgets. You’ll get up to speed with Linux so that you can install secure, fully functioning Linux server systems
Keywords: Linux ( computer programs ),Linux ( chương trình mạng máy tính)